Harmonisasi Nilai Adat dan Hukum Negara: Analisis Putusan Perkara Nomor 94/PDT.G/2022/PN JAP (International Forum of Researchers and Lecturers, 2024)
Indonesia, as a country with a pluralistic legal system, faces challenges in harmonizing customary law and state law, particularly in resolving disputes over customary land that involve traditional values of indigenous communities. This study aims to analyze how customary values are integrated with state law through a case study of court decision Number 94/Pdt.G/2022/PN Jap. The research employs a qualitative approach with content analysis techniques applied to court decision documents, supported by relevant literature reviews. The findings reveal that the court in this case not only applied positive legal norms but also considered relevant customary aspects, including the legitimacy of indigenous leaders and the recognition of communal land rights (ulayat). The panel of judges issued a decision that accommodated customary values in accordance with Article 18B paragraph (2) of the 1945 Constitution, while still adhering to the formal procedures of state law. This study identifies challenges in integrating customary law into the national legal system, such as the lack of formal regulations related to customary courts and the limited understanding of legal officers regarding local cultural contexts.